O otroštvu v srednjem veku (Trst, Koper, Izola, Piran) - Mihelič, Darja (Etnolog. Nova vrsta (Ljubljana), 2007)
The article deals with the history of children in the medieval towns of Trieste, Koper, Izola, and Piran. It is based on documents, notarial and vicedominus records from the Piran branch office of the Regional Archives of Koper, covering the period up to the mid 14th century, and preserved medieval town codes of law, called statutes from the 14th and 15th centuries. Based on the provisions of the statutes, the article first describes the position of children and family relationships, inheritance and property division, the position of orphans, coming of age, legal capacity and criminal liability of children, children as delinquents and as victims of criminal offences; it then confronts these provisions with the documented practices in Piran and established that they were largely in line with the legislation.
Keywords: child; otroci; Trst; children; družbeni položaj; social status; srednji vek; Koper; Middle Ages; Izola; Trieste; Piran; Capodistria; Isola; Pirano